Enhanced Mechanical Properties and Degradation Control of Poly(Lactic) Acid/Hydroxyapatite/Reduced Graphene Oxide Composites for Advanced Bone Tissue Engineering Application - Francis T. Omigbodun; Bankole I. Oladapo (Biomimetics)
This study explores the enhancement of poly(lactic acid) (PLA) matrix using calcium hydroxyapatite (cHAP) and reduced graphene oxide (rGO) for developing composite scaffolds aimed at bone regeneration applications. The PLA composites were fabricated through solvent evaporation and melt extrusion and characterized by various techniques, including thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and mechanical testing. The incorporation of cHAP and rGO significantly improved the thermal, mechanical, and morphological properties of the PLA matrix. Mechanical testing revealed that adding 10% cHAP and varying amounts of rGO (0.1%, 0.3%, 0.5%) enhanced tensile and compressive strengths, with the highest improvements observed at 0.5% rGO content. Thermal analysis showed increased thermal stability with higher degradation temperatures for the composites. Spectroscopic analyses confirmed the effective integration of cHAP and rGO into the PLA matrix with characteristic peaks of the fillers identified in the composite spectra. In vitro, degraded action tests in phosphate-buffered saline (PBS) at pH 7.4 over 12 months indicated that composites with higher rGO content exhibited lower mass loss and better mechanical stability. Furthermore, finite element analysis (FEA) simulations were performed to validate the experimental results, demonstrating a strong correlation between simulated and experimental compressive strengths. This novel approach demonstrates the potential of PLA/cHAP/rGO composites in creating effective and biocompatible scaffolds for tissue engineering, providing a comprehensive analysis of the synergistic effects of cHAP and rGO on the PLA matrix and offering a promising material for bone regeneration applications.